2005
DOI: 10.1007/s00595-004-3050-8
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Effects of Two Types of Bioresorbable Barriers to Prevent Postoperative Intra-Abdominal Adhesions in Rats

Abstract: Neither material prevented adhesions in clean contaminated conditions. Moreover, they increased adhesion formation in bacterial peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…during the crucial 12–36 h) after surgery. The primary mode of adhesion prevention is likely due to the HA film forming a credible, initial physical barrier between damaged tissues to resist cells migrating from the defect surfaces to ‘bridge’ and subsequently evolve into fibrous tissue [37,38]. Furthermore, the intrinsic properties of HA could enable the HA film to serve as the equivalent of a lubricating surface to discourage significant cell attachment [22,26,39].…”
Section: Discussionmentioning
confidence: 99%
“…during the crucial 12–36 h) after surgery. The primary mode of adhesion prevention is likely due to the HA film forming a credible, initial physical barrier between damaged tissues to resist cells migrating from the defect surfaces to ‘bridge’ and subsequently evolve into fibrous tissue [37,38]. Furthermore, the intrinsic properties of HA could enable the HA film to serve as the equivalent of a lubricating surface to discourage significant cell attachment [22,26,39].…”
Section: Discussionmentioning
confidence: 99%
“…By minimizing the development of the fibrin matrix between serosal tissue surfaces, such membranes may prevent adhesion formation. 8 At present, sodium hyaluronate-carboxymethyl cellulose (Seprafilm, Genzyme Corporation, Cambridge, MA, USA) is the most common adhesion prevention product that has been studied in randomized controlled clinical trials. Multiple studies have demonstrated that this barrier membrane significantly and safely decreases the incidence, extent, and severity of adhesion formation.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicate that peritoneal lavage promotes adhesion formation, as opposed to reports that suggested a preventive role for peritoneal lavages in adhesion formation. [26][27][28] Antibiotics can exert their anti-adhesive effects by inhibition of synthesis or expression of adhesins on the bacterial cell surface, or modify bacterial protein expression in such a way as to interfere with the ability of the microorganisms to approach receptors on animal cell surface. [29] Sortini et al [5] compared the efficacy of peritoneal lavage with chloramphenicol, clindamycin, piperacillin, tobramycin, ceftriaxone and imipenem-cilastatin to saline, with adhesion formation increased in study groups.…”
Section: Discussionmentioning
confidence: 99%